1999
DOI: 10.3109/08916939908995967
|View full text |Cite
|
Sign up to set email alerts
|

A 63 kDa Skeletal Muscle Protein Associated with Eye Muscle Inflammation in Graves' Disease is Identified as the Calcium Binding Protein Calsequestrin

Abstract: It is generally accepted that thyroid-associated ophthalmopathy (TAO) is an autoimmune disease of the eye muscle (EM) and the surrounding orbital connective tissue in which circulating antibodies play an important role. Antibodies against EM membrane proteins of 63-67kDa mol. wt. seem to be the best markers of ophthalmopathy in patients with autoimmune thyroid disease. We purified a 63 kDa EM protein using SDS-polyacrylamide gel electrophoresis technology and TAO patients' sera as probes, digested the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…However, none of the target antigens are localized exclusively in the eye muscle and all are intracellular, suggesting that their exposure to the immune system would be a consequence of eye muscle fiber damage (4) rather than its cause. In the present study, we have measured serum antibodies against the three main candidate eye muscle antigens, namely i) the 67-kDa flavoprotein (Fp) subunit of the mitochondrial enzyme succinate dehydrogenase, which is expressed in extraocular and systemic skeletal muscle fibers, but not in the thyroid (13,14); ii) G2s, the terminal 141 amino acid fragment of the winged-helix transcription factor FOXP1, which is expressed in the nuclei and cytoplasm of many cell types including the eye muscle fiber (15,16); and iii) calsequestrin, a 63-kDa calcium binding protein that is expressed in eye muscle and other skeletal muscle, but not in the thyroid (17). Another putative target of autoimmunity in the orbit that was addressed in the present study is the fibroblast cell membrane protein collagen type XIII.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the target antigens are localized exclusively in the eye muscle and all are intracellular, suggesting that their exposure to the immune system would be a consequence of eye muscle fiber damage (4) rather than its cause. In the present study, we have measured serum antibodies against the three main candidate eye muscle antigens, namely i) the 67-kDa flavoprotein (Fp) subunit of the mitochondrial enzyme succinate dehydrogenase, which is expressed in extraocular and systemic skeletal muscle fibers, but not in the thyroid (13,14); ii) G2s, the terminal 141 amino acid fragment of the winged-helix transcription factor FOXP1, which is expressed in the nuclei and cytoplasm of many cell types including the eye muscle fiber (15,16); and iii) calsequestrin, a 63-kDa calcium binding protein that is expressed in eye muscle and other skeletal muscle, but not in the thyroid (17). Another putative target of autoimmunity in the orbit that was addressed in the present study is the fibroblast cell membrane protein collagen type XIII.…”
Section: Introductionmentioning
confidence: 99%
“…The ELISA has been described in previous publications from this laboratory 15,16 and is standard. G2s fusion protein was purified using a pFLAG ATS E. coli expression system as described previously, human recombinant Fp (kindly donated by Dr. Brian Ackrell, UCSF, CA), highly purified rabbit skeletal muscle calsequestrin, which has 97% homology with human calsequestrin (supplied by Dr. Nicole Beard, ANU, Canberra, Australia), and recombinant human collagen XIII (provided by Drs.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…More recently, we showed that a small proportion of patients with TAO had peripheral T cells which were sensitised to recombinant human G2s [20]. In the present study, we have tested for blood T lymphocyte-mediated reactivity against three eye muscle antigens, calsequestrin [21], Fp [22] and a 141 amino acid fragment of the winged-helix transcription factor FOXP1 that we call G2s [23], in patients with Graves' ophthalmopathy (GO), Graves' hyperthyroidism (GH) without ophthalmopathy and age and sex matched normal subjects using a standard lymphocyte proliferation assay. We demonstrated highly significant T lymphocyte-mediated reactivity against calsequestrin and Fp, but not G2s, in patients with ophthalmopathy, especially those with active, recent onset and disease.…”
Section: Introductionmentioning
confidence: 96%